ANALISIS SURVIVAL KEJADIAN LOSS TO FOLLOW-UP TERAPI ANTI- RETROVIRAL (ARV) PADA PASIEN HIV DI KOTA SAMARINDA: LOSS TO FOLLOW-UP TERAPI ANTI- RETROVIRAL - Utami, Dian Margi; Wisnuwardani, Ratih Wirapuspita; Saefurrohim, Muhamad Zakki (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Loss to follow (LTFU) -up among HIV patients, defined as failure to continue therapy as schduled, increases the risk of drug resistance, deteriorating health conditions, and death due to HIV-related complications. This study aimed to analyze the survival of HIV patients againts LTFU events among those undergoing antiretroviral therapy (ARV) in Samarinda City. Secondary data from the SIHA database (2023-2024) were utilized. Kaplan-Meier analysis was applied to evaluate the factors of gender, residence, population group, and timing of ARV initiation associated with the risk of LTFU. The results showed that gender and residance were not significantly associated with the risk of LTFU. However, specific population groups, such as children of PLHIV and pregnant women, exhibited higher vulnerability and lower survival rates (log rank = 0.015). ART initiation within ≤ 1 month significantly improved survival probability compared to initiation after > 1 month. These finding highlight that while gender and residance do not significantly influence LTFU, the vulnerability of spesific populations and the critical importance of early ART initiation are key factors. It is recommende to develop targeted interventions focusing on vulnerable groups, such as children of PLHIV and pregnant women, to enhance their survival rate. Additionally, strategies promoting ART initiation within ≤ 1 month are esential to improve treatment sustainability.